Establishment and application of a dual chip digital PCR assay for detection of PDCoV and PEDV - Zhang, Yue; Dong, Fangting; Zhang, Yuhang; Feng, Yutong; Hu, Jinwang; Li, Yuhang; Xia, Lu; Zu, Shaopo; Lu, Hao; Wei, Zhanyong (Frontiers in Veterinary Science, 2025)
IntroductionCoinfection with porcine deltacoronavirus (PDCoV) and porcine epidemic diarrhea virus (PEDV) is a major cause of acute diarrhea in piglets, which poses a significant challenge to the swine industry. The early detection and control of these two viruses require highly sensitive diagnostic tools. We developed a novel chip digital PCR (cdPCR) assay that uses two probes for the simultaneous quantitative detection of both PDCoV and PEDV in clinical samples.MethodsIn this study, the dual cdPCR reaction system, including the annealing temperature and primer–probe concentration ratio, was systematically optimized. Additionally, we validated the developed method for specificity, sensitivity, linearity, and repeatability. Finally, the method was applied to assess the biological samples with low viral loads.ResultsThe dual cdPCR assay demonstrated exceptional sensitivity, with limits of detection (LoD) of 1.83 ± 0.15 copies/μL for PDCoV and 0.99 ± 0.07 copies/μL for PEDV, high specificity (no cross-reactivity with TGEV, PSV, or PRV), outstanding linearity (R2 = 0.9972 for PDCoV and R2 = 0.9969 for PEDV) and reproducibility (intra- and inter-assay CV < 6%). Validation across 148 clinical samples indicates that our dual cdPCR is more sensitive than qPCR for detecting both single and mixed infections. Notably, this assay can effectively quantify PDCoV and PEDV in environmental aerosol samples.DiscussionOur results demonstrate that this dual cdPCR assay offers a highly sensitive, stable, and accurate platform for the simultaneous quantification of both PDCoV and PEDV. It represents a valuable tool for early disease monitoring (particularly in aerosol surveillance and mixed-infection scenarios with low viral loads), thereby supporting the effective prevention of porcine viral diarrhea and the sustainable growth of the swine industry.